2013
DOI: 10.1111/j.1365-2265.2012.04490.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function measured using flow‐mediated dilation in polycystic ovary syndrome: a meta‐analysis of the observational studies

Abstract: This systematic research synthesis indicates that endothelial function is compromised in PCOS women, even if they are young and nonobese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 49 publications
5
88
1
5
Order By: Relevance
“…This is reflected in impaired endothelial function as measured by flowmediated dilation of the brachial artery, already at an early age and confirmed by the recent meta-analysis (193). Besides the early functional impairment of the vascular wall, the morphologic signs of early atherogenesis as increased intima-media thickness of carotid arteries (C-IMT) are highly prevalent in young women with PCOS (194,195,196).…”
Section: Cardiometabolic Risk In Pcos: the Heart Of The Problemmentioning
confidence: 52%
“…This is reflected in impaired endothelial function as measured by flowmediated dilation of the brachial artery, already at an early age and confirmed by the recent meta-analysis (193). Besides the early functional impairment of the vascular wall, the morphologic signs of early atherogenesis as increased intima-media thickness of carotid arteries (C-IMT) are highly prevalent in young women with PCOS (194,195,196).…”
Section: Cardiometabolic Risk In Pcos: the Heart Of The Problemmentioning
confidence: 52%
“…147,148 A meta-analysis of several studies reported a significant decrease in flow-mediated endothelial dilation associated with PCOS after accounting for age and BMI, although there was substantial heterogeneity between studies. 149 Differences in carotid intima-media thickness and impairment in peripheral vascular function could be attributed at least in part to insulin resistance, obesity, or dyslipidemia. 144,[150][151][152][153][154][155] Although a few studies report greater CAC in women with PCOS than in those who do not have PCOS, [156][157][158][159] these data must be interpreted cautiously because of the influence of obesity on CAC measurements and the low prevalence of detectable CAC among young women (5.1% of women 33-45 years of age).…”
Section: Pcos and Surrogates For Cvdmentioning
confidence: 99%
“…The risk of publication or other biases was detected when assessing the SMD in endothelial function. However, the quality of studies was evaluated by specific tools for the quality assessment of observational research, 81,82 revealing a predominantly low-bias risk. It must be acknowledged that the ethnicity of the populations was poorly reported by studies included in this meta-analysis, and thus, conclusions on the effect of ethnicity cannot be drawn from these data.…”
mentioning
confidence: 99%